Pendidikan Kesehatan Tentang Rheumatoid Arthritis dan Senam Rematik Pada Lansia - Mardiono, Sasono; Saputra, Andre Utama (Nanggroe: Jurnal Pengabdian Cendikia, 2025)
Rheumatoid arthritis or better known as rheumatism is a progressive autoimmune disease with chronic inflammation that attacks the musculoskeletal system but can involve organs and body systems as a whole. The purpose of this activity is to provide health education about rheumatoid arthritis and rheumatic exercises. The method of implementing this Community Service Program is community education in the form of health counseling, evaluated by pre-test and post-test The method of implementing the service is by providing Rheumatic Exercises. The number of participants who attended was 30 people, 2 of whom were students. The activity started from the planning, implementation, evaluation, to the preparation of the report. The results of the joint pain scale before the intervention were obtained in the elderly who experienced mild pain as many as 2 people (6.7%), moderate pain 27 people (90.0%), and severe pain 1 person (3.3%). Meanwhile, the results of the joint pain scale after the intervention were found to have changed, where there were no more elderly people experiencing severe pain and moderate pain, elderly people experiencing mild pain were 28 people (93.3%) and no pain were 2 people (6.7%). It is hoped that this activity can be a health promotion strategy in the prevention and control of rheumatoid arthritis.